Are Top-down Approaches of Transitional Justice Enough to Deliver Justice? To what extent can transitional justice from below tackle the contemporary problems of doing justice after mass violence? (TEST Trento Student Law Review, 2022)
The aim of the article is to shed light on the values of transitional justice from below: this peculiar approach fits in the whole process of transition towards democracy, peace, and reconciliation and constitutes a praiseworthy course of action to deliver justice after mass atrocities have been perpetrated during a conflict. To begin with, the “bottom-up approach” will be analyzed. Secondly, the article will consider the specular “top-down approach” by pointing out its deficiencies. The call for an enriched transitional process that considers the needs and the will of the affected communities comes from civil society itself; if not, it is feared that the whole process might be perceived as illegitimate, compromising the entire transition. In fact, civil society, in its various forms, is a key player that can benefit the transitional process. After these introductory remarks, the article tries to investigate the ideal role that civil society should play when governmental institutions of a particular country obstruct, or at least, do not undertake, initiatives of transitional justice. It goes without saying that not even bottom-up initiatives are free from criticism.
Keywords: Transitional justice; Justice "from below"; Conflicts and mass atrocities; Civil society; Reconciliation